Intention of Mobile Phone Users to Use Fitness and Health Applications to Manage and İmprove Their Health - Harshraj Sejpal (International Journal of Advanced Science and Technology, 2020)
The paper tries to find out and understand the many reasons behind a mobile phone user’s intention to use fitness and health applications to manage and improve his/her health. The paper covers this scenario in past, present and future context. Over the past few years, there have been the launches of thousands of fitness and health mobile applications. The category of these applications is among the top 10 categories in both the Google Play Store and the Apple App Store. The focus should be on why these applications are proving to be of use to millions of mobile phone users worldwide. The goal of this paper is to find out the factors which have and which will affect the intention of a mobile phone user to use a fitness/health application. Mathematical concepts such as Cronbach’s Alpha to prove reliability, mean and correlation using Spearman Rank Correlation Coefficients were applied to analyze the formulated hypotheses. Five determinants were found to have an effect on the intention of use of these applications. These determinants are usefulness of an application, trust propensity, recordability of information via such an application, social facilitation features in an application and the ease of operating an application.